The Influences of Asset Structure and Asset Growth Toward Capital Structure - Hanifa Nur Fadhilla (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2023)
This research is aimed to investigate the influence of asset structure and asset growth toward capital structure. This study examines the factors influencing capital structure in real estate and property companies. This study used samples of 21 companies in its sector listed in Indonesia Stock Exchange (IDX) 2018-2020. The hypotheses are examined using two models to support the factors influencing capital structure. The result of this research expressed that from two independent variables, there is independent variable in particularly asset structure that have positive significance influence toward capital structure. Hypothesis of asset structure is accepted. However, another independent variable specifically asset growth does not influence capital structure. Thus, the hypotheses are rejected. This research result derives from t-test statistics.